Hematopoietic stem cell transplantation in children and adolescents with GATA2-related myelodysplastic syndrome - Bortnick, Rachel; Wlodarski, Marcin; de Haas, Valerie; De Moerloose, Barbara; Dworzak, Michael; Hasle, Henrik; Masetti, Riccardo; Starý, Jan; Turkiewicz, Dominik; Ussowicz, Marek; Kozyra, Emilia; Albert, Michael; et al. (Bone marrow transplantation, 2021)
GATA2 deficiency is a heterogeneous multi-system disorder characterized by a high risk of developing myelodysplastic syndrome (MDS) and myeloid leukemia. We analyzed the outcome of 65 patients reported to the registry of the European Working Group (EWOG) of MDS in childhood carrying a germline GATA2 mutation (GATA2mut) who had undergone hematopoietic stem cell transplantation (HSCT). At 5 years the probability of overall survival and disease-free survival (DFS) was 75% and 70%, respectively. Non-relapse mortality and relapse equally contributed to treatment failure. There was no evidence of increased incidence of graft-versus-host-disease or excessive rates of infections or organ toxicities. Advanced disease and monosomy 7 (-7) were associated with worse outcome. Patients with refractory cytopenia of childhood (RCC) and normal karyotype showed an excellent outcome (DFS 90%) compared to RCC and -7 (DFS 67%). Comparing outcome of GATA2mut with GATA2wt patients, there was no difference in DFS in patients with RCC and normal karyotype. The same was true for patients with -7 across morphological subtypes. We demonstrate that HSCT outcome is independent of GATA2 germline mutations in pediatric MDS suggesting the application of standard MDS algorithms and protocols. Our data support considering HSCT early in the course of GATA2 deficiency in young individuals.
Keywords: Hematopoietic Stem Cell Transplantation; myelodysplastické syndromy; Child; zárodečné mutace; transplantace hematopoetických kmenových buněk; transkripční faktor GATA2; Myelodysplastic Syndromes; Adolescent; Germ-Line Mutation; Humans; lidé; chromozomální delece; nemoc štěpu proti hostiteli; Chromosome Deletion; GATA2 Transcription Factor; dítě; Graft vs Host Disease; mladiství